PATTERNS OF SOCIAL MOVEMENT AND LAND ACQUISITION IN WATESJAYA VILLAGE, BOGOR REGENCY - Fajar Imani Nurismawan; Rina Mardiana; Titik Sumarti (SOSIOEDUKASI, 2025)
Social movements in Watesjaya Village, Cigombong District, Bogor Regency, emerged in response to the massive land acquisition by PT MNC Land for the development of the Lido Special Economic Zone (KEK Lido). This practice encourages massive land conversion that has a direct impact on the survival of local communities, especially forest and non-forest area farmers who have worked on the land for generations. This research uses a qualitative approach involving in-depth interviews with key actors, direct observation in the field, and archival searches. The two main actors, forest area and non-forest area farmers, showed different resistance movements. Farmers in forest areas use an adaptive approach through forest utilization and ecotourism management under the Social Forestry scheme with a Conservation Partnership Agreement (PKK), while the resistance movement of non-forest area farmers uses protests, demonstrations, and rejection of unfair compensation. These different approaches reflect variations in resource mobilization, local knowledge, and level of organization with impacts varying from delaying eviction to creating alternative livelihoods.